(untitled) (Revista Nacional de Odontología, 2014)
Introduction: to determine the prevalence of joint noise among 20-year-old university students in Pasto, Nariño, Colombia. Methods: The sample consisted of 173 individuals (77 men and 96 women), who were evaluated according to Temporomandibular Disorder Research Diagnostic Criteria (rdc/tmd Spanish version) Axis. Results: 36 individuals (20.8%) had joint noise; 32 (18.8%) were clicking and 4 (2%) had crepitation. The women/men ratio was 1.7:1 (p > 0.05). Individuals studying a health science career had a higher joint noise rate. In relation to joint noise characteristics, 24 temporomandibular joints (tmj) had clicking/crepitation at the reproducible aperture and 14 had clicking/crepitation at the reciprocal aperture. Additionally, 19 tmj had clicking/crepitation at the reproducible closure and 14 had clicking/ crepitation at the reciprocal closure. 18 (50%) students with joint noise had limited aperture; 68 (39.3%) students had muscular or joint pain when palpated; 17 individuals (47.2%) with joint noise had muscular or joint pain when palpated. Conclusion: The results show the clinical characteristics of joint noise among university students. The prevalence is similar to what is reported among other populations; there is an insignificant difference according to gender, and almost half of those with joint noise had muscular or joint pain when palpated. The presence of clicking is a good indicator of disk displacement with reduction.